Adaptation and validation of scales to measure self-efficacy and empowerment for self-care in Mexican climacteric stage women. - Svetlana V Doubova; Patricia Espinosa-Alarcón; Claudia Infante; Rebeca Aguirre-Hernández; Leticia Rodríguez-Aguilar; Roberto Olivares-Santos; Ricardo Pérez-Cuevas (Instituto Nacional de Salud Pública, 2013)
Objective. To adapt and validate in Spanish of Mexico scales to measure self-efficacy (SES) and empowerment for self-care (ES) among climacteric women. Materials and methods. The study was conducted from February to July 2011 in two family medicine clinics in Mexico City. The adaptation phase was done through testing for language comprehension. To validate the scales we used the principal Axis factoring analysis with oblique rotation technique and estimation of Cronbach's alpha (CA). Results. Three hundred eighty women aged 45-59 years participated in the study. SES had 16 items with four factors: participation in the doctor-patient relationship; in the study control of mental health and sexual changes; risk of dying from cancer, and other health risks that explained 39.8% of the variability, CA= 0.84. ES had eight items with one factor explaining 47.1% variability; CA= 0.83. Conclusion. Both scales had acceptable psychometric properties and are suitable for interventions aimed at improving self-care of climacteric women.